CHILD POVERTY TYPOLOGIES AND PROTECTIVE FACTORS IN SCAVENGER COMMUNITIES: IMPLICATIONS FOR PARTICIPATORY SOCIAL DEVELOPMENT STRATEGIES - ferezagia, debrina vita; Musthofa, Budiman Mahmud (UI Scholars Hub, 2026)
This study aims to develop a typology of child poverty and identify protective factors that can support the formulation of social development strategies. The research was conducted through a case study in a scavenger settlement area in Jakarta using a qualitative approach, through observations and in-depth interviews. The findings show that child poverty in scavenger communities can be categorized into three main dimensions: material poverty, opportunity poverty, and relational poverty. However, behind these vulnerabilities, several protective factors play a crucial role in sustaining the resilience of both children and the community. In the dimension of material poverty, although children face limitations in accessing basic needs, family social support emerges as the primary protective factor. In the dimension of opportunity poverty, some children continue to demonstrate high learning motivation and adaptability despite not being enrolled in formal schools. The presence of social institutions, volunteer educators, and non-formal learning activities within the settlement serves as institutional protective factors that provide children with opportunities to acquire basic skills and broaden their knowledge. Meanwhile, in the dimension of relational poverty, although children experience social stigma, emotional support from the community functions as an important psychosocial protective factor. Based on these findings, social development strategies are directed toward strengthening protective factors through participatory and integrative approaches. Interventions should not only focus on meeting individual welfare needs but also on building the capacities of families and communities as social ecosystems that support children's growth and development.